EVALUATING THE BIOCONCENTRATION FACTORS (BCF) AND ESTIMATED DAILY INTAKE (EDI) OF HEAVY METALS IN LIME PLANTS (CITRUS AURANTIFOLIA) IN SMALL SCALE GOLD ORE PROCESSING AREAS - Febriansyah, Febriansyah; Lijaya, Albadi; Rukmini, Rukmini; Amallia, Ra. Hoetary Tirta; Teristiandi, Novin; Saputra, Andi; Soleha, Siti (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Small-scale gold ore processing areas have become a global concern due to their significant contribution to heavy metal pollution. The residual amalgamation process in these areas leads to the accumulation of heavy metals in the environment, which can bioaccumulate in living organisms. This study focuses on the lime plant (Citrus aurantifolia), commonly found in small-scale gold ore processing areas, particularly in Sukamenang village. The research aims to assess the Bioconcentration Factor (BCF) and Estimated Daily Intake (EDI) of heavy metals in lime plants to evaluate the risk to residents who consume them. Samples were collected using random sampling and analyzed with an Atomic Absorption Spectrophotometer (AAS) and a mercury analyzer. The results indicate that Citrus aurantifolia has a BCF value of less than 1 (<1), classifying it as an excluder plant, effectively preventing heavy metals from entering its upper parts and allowing it to thrive in polluted environments. However, the consumption of these plants poses health risks. The study highlights the Reference Dose (RfD) values for heavy metals: Cu at 4.0 x 10^-2 (0.008), Fe at 0.7, and Hg at 0.0001, as recommended by the United States Environmental Protection Agency (USEPA) in 2011. Heavy metals such as Fe, Cu, and Hg in the lime plants indicate potential adverse health effects due to their toxicity. This research underscores the necessity for monitoring and mitigating heavy metal pollution in small-scale gold ore processing areas to protect public health and the environment.